Exploring an evolutionary traffic flow landscape with a fitness approach - Kingsley E. Haynes; Rajendra G. Kulkarni; Roger R. Stough (Penerbit Universiti Kebangsaan Malaysia, 2007)
The road patterns of major metropolitan areas and constituent jurisdictions evolve slowly through a complex set of independent and interdependent decisions producing a transportation network. The resulting network must be used for variety of commuting and spatial interaction activity. A typical trip taker spends considerable time on the road to reach the workplace and other destinations. Adding more links to existing roadnetworks and/or increasing trafic capacity by adding lanes does not necessarily decrease travel times. However, a dense redundant network of roads provides a trip laker with alternate routes when traflic congestion occurs. Such issues raise the question of, how to evaluate the flow characteristics of the entire road network of a jurisdiction or its larger region? We explore a methodology to evaluate fitness criteria for road networks based on KaufSman 's evolutionary complexity or NK model (1993) and develop an information theoreric measure of the order or organization in transportation networks. ASSTRAK Bentuk jalanraya bagi kawasan metropolitan dan kawasan sekitar berubah perlahan-lahan melalui rangkaian pengangkutan yang kompleks sama ada secara bebas atau bergantungan antara satu sama lain. Rangkaian ini perlu digunakan untuk pelbagai aktiviti perhubungan dan interaksi ruang. Seorang pengguna jalanraya mengambil masa yang agak lama untuk sampai ke tempat kerja dan destinasi lain yang dituju. Dengan rnenambahkan lebih banyak hubungan kepada jalanraya sedia ada tidak semestinya mempercepatkan masa perjalanan. Walau bagairnanapun, rangkaian jalanraya yang padat menyediakan pengguna jalanraya dengan jalan-jalan alternutif apabila berlakunya kesesakan. Isu ini menimbulkan persoalan seperti bagaimana menilai ciri-ciri aliran dalam rangkaian jalan di pelbagai wilayah? Kita mencuba satu kaedah untuk menilai kriteria kesesuaian bagi rangkaian jalan raya berdasarkan kepada kekompleksan evolusi Kauffman atau model NK (1993) dun mengembangkan satu ukuran maklumat secara teori bagi susunan atau organisasi yang berkait dengan rangkaian pengangkutan.